KAJIAN NILAI MARSHALL CAMPURAN BETON ASPAL (AC) DENGAN MENGGUNAKAN RETONA BLEND 55 SEBAGAI BAHAN ADITIF - Ishak Ishak (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
One type of flexible pavements that have a high structural value is asphalt concrete. Asphalt concrete is widely used in Indonesia’s roads with a high service level. Asphalt concrete is composed of aggregates of several factions that have a certain gradation using asphalt binder.This study uses asphalt concrete (AC) with a variation of Retona Blend 55 levels of 0%, 0.5%, 1%, 1.5%, 2%. Asphalt concrete mix then compacted at a temperature of 1600C. The test specimen then immersed in waterbath at a temperature of 600C with a immersion time of 0.5 hours and 24 hours. Then testing Marshall characteristics.Addition levels of Retona Blend 55 generates the value of of stability and higher density values. Instead VITM (void in the mix) value, flow rate, and the value of VFWA (Void Filled With Asphalt) lower.Keywords: Beton Aspal, Retona Blend 55; karakteristik  Marshall